Optimal Antithrombotic Treatment of Patients with Atrial Fibrillation Early after an Acute Coronary Syndrome—Triple Therapy, Dual Antithrombotic Therapy with an Anticoagulant… Or, Rather, Temporary Dual Antiplatelet Therapy? - Limbruno, Ugo (J Clin Med, 2020)
The combination of atrial fibrillation (AF) and acute coronary syndrome (ACS) is a complex situation in which a three-dimensional risk—cardioembolic, coronary, and hemorrhagic—has to be carefully managed. Triple antithrombotic therapy (TAT) is burdened with a high risk of serious bleeding, while dual antithrombotic therapy with an anticoagulant (DAT) likely provides only suboptimal coronary protection early after stent implantation. Moreover, TAT precludes the advantages provided by the use of the latest and more potent P2Y(12) inhibitors in ACS patients. Here, we aimed to simulate and compare the expected coronary, cardioembolic, and hemorrhagic outcomes offered by DAT, TAT, or modern dual antiplatelet therapy (DAPT) with aspirin plus one of the latest P2Y(12) inhibitors in AF patients early after an ACS. The comparison of numbers needed to treat to prevent major adverse events with the various antithrombotic regimens suggests that AF–ACS patients at high ischemic and hemorrhagic risk and at moderately low embolic risk (CHA(2)DS(2)VASc score 2–4) might safely withhold anticoagulation after revascularization for one month taking advantage of a modern DAPT, with a favorable risk-to-benefit ratio. In conclusion, this strategy, not sufficiently addressed in recent European and North American guidelines or consensus documents, adds to the spectrum of treatment options in these difficult patients; it might be the best choice in a substantial number of patients; and should be prospectively tested in a randomized controlled trial.